Self-assembly of silica particles in a nonionic surfactant hexagonal mesophase - Sharma, Kamendra P.; Kumaraswamy, Guruswamy; Ly, Isabelle; Mondain-Monval, Olivier (Journal of Physical Chemistry B, 2009)
We investigate the process of self-assembly, and the resultant structures in composites of silica particles with a hexagonal mesophase of a nonionic surfactant and water. We report a systematic transition in behavior when the particle size is increased relative to the characteristic mesophase spacing. Water dispersible cage-like silsesquioxanes that are molecular analogues of silica particles and are smaller than the mesophase spacing swell the space between the surfactant cylinders. Silica particles comparable to the characteristic hexagonal spacing partition into the hexagonal phase and into strandlike particulate aggregates. Even larger particles phase separate from the hexagonal phase to form particulate strands that organize with a mesh size comparable to the wavelength of visible light. This self-assembly is reversible and the particles disperse by breaking up the aggregates on heating the composite into the isotropic phase. On cooling from the isotropic phase into the hexagonal, the particles are expelled from the growing hexagonal domains and finally impinge to form strandlike aggregates. Unusually, the isotropization temperature is increased in the composites as the particles nucleate the formation of the hexagonal phase.